2006
DOI: 10.1080/02671520500335907
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting value systems: Gypsy females and the home‐school interface

Abstract: Drawing on data from a three-year ethnographic study of Gypsy life in England, this article explores the experience and attitudes of Gypsy women regarding the home-school interface. Specific attention is given to the following: role expectations in the different contexts; changing perceptions of role in the face of economic and social change; the contradictions and tensions arising from the process of schooling; and the identity dilemmas experienced by those young women who remain in the educational system. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 6 publications
0
17
0
2
Order By: Relevance
“…Finalmente, la relación entre matrimonio adolescente y fracaso escolar ha sido puesta de manifiesto en estudios anteriores (Čvorović, 2004Levinson y Sparkes, 2006;Martín y Gamella, 2005). El matrimonio temprano no debe verse como una tradición inamovible que corresponda a una identidad étnica inalterable.…”
Section: Factores Clave En El Abandono Escolarunclassified
“…Finalmente, la relación entre matrimonio adolescente y fracaso escolar ha sido puesta de manifiesto en estudios anteriores (Čvorović, 2004Levinson y Sparkes, 2006;Martín y Gamella, 2005). El matrimonio temprano no debe verse como una tradición inamovible que corresponda a una identidad étnica inalterable.…”
Section: Factores Clave En El Abandono Escolarunclassified
“…School engagement is thus perceived as potentially dangerous, as it could weaken cultural identity and attract the next generation of Gypsies away from their own social sphere (Clay, 1999). In a study by Levinson and Sparkes (2006), it was found that Gypsy parents could become estranged by their community if they allowed their children to stay on at secondary school, as this was seen as a manifestation of group disloyalty (p. 93). Jordan (2001) and others have even suggested that some Gypsy parents may maintain cultural boundaries by citing bullying (as an excuse) to justify their rejection of secondary education.…”
Section: Pull Factorsmentioning
confidence: 95%
“…The requirement to operate within a dual cultural framework regularly brought them into conflict with both their families and Gypsy Traveller peers as well as with their teachers and nonTraveller peers as they attempted to balance oscillating loyalties. In their recent study of Gypsy females and the home-school interface, Levinson and Sparkes (2006) suggested that this intrinsic discord could cause psychosocial difficulties for those who stay on in the education system without having developed effective coping strategies to assuage the discomfort.…”
Section: Coping Strategiesmentioning
confidence: 98%
“…With regard to my own work, such tensions have emerged on the basis of gender (Levinson & Sparkes, 2006), age-group, patterns of work and lifestyle (Levinson & Sparkes, 2004).…”
Section: Fieldnotes March 1998 Site D Devonmentioning
confidence: 99%